Analysis and estimation of the transport expenses under conditions of its reformation - Barash, Yu. S.; Pshinko, O. M.; Lomtieva, I. N. (Science and Transport Progress, 2010)
In the article the methods of analysis and estimation of expenses at railway transport enterprises aimed at management of the enterprise cash flows and all possible ways of grouping and cost sharing on the railway transport in the conditions of its reformation are considered.